Clearance of refractory bile duct stones with Extracorporeal Shockwave Lithotripsy: higher failure rate in obese patients. (February 2014) - Lenze, Frank; Heinzow, Hauke S.; Herrmann, Edwin; Berssenbrügge, Christoph; Rothenbächer, Helen; Ullerich, Hansjörg; Floer, Martin; Domschke, Wolfram; Domagk, Dirk; Meister, Tobias
Abstract Objective. Bile duct stones that cannot be removed endoscopically are still a challenge in interventional gastroenterology. Extracorporeal shockwave lithotripsy (ESWL) with subsequent endoscopic extraction of residual fragments is an established treatment option if other endoscopic means are not successful. Our study aimed to investigate the efficacy and safety of ESWL for clearance of refractory bile duct stones. Material and methods. A total of 73 consecutive patients treated for refractory choledocholithiasis with ESWL were retrospectively analyzed. Success and complication rates were calculated. Results. Complete stone clearance was achieved in 66 cases (90%). Patients with complete clearance had a significantly lower body mass index or BMI (25.55 ± 5.01 kg/m2 vs. 31.60 ± 6.26 kg/m2, p = 0.035) and needed less ESWL treatments (3.61 ± 1.87 vs. 5.00 ± 1.63, p = 0.048). A relevant drop of hemoglobin occurred significantly more often in the group with partial clearance (43% vs. 6%, p = 0.005). Conclusions. ESWL proves to be an excellent clearing approach to refractory bile duct stones with high success rates. However, obesity is one risk factor for ESWL failure and higher procedural hazard.